Conjugate Alkynylation of Electrophilic Double Bonds. From Regioselectivity to Enantioselectivity - Blay, Gonzalo; Pedro, José R.; Sanz-Marco, Amparo (Synthesis, 2018)
This review surveys the historical efforts addressed toward the development of the conjugate alkynylation reaction. The regio- and enantioselective conjugate alkynylation of electron-deficient double bonds, most commonly unsaturated carbonyl compounds, has been an elusive reaction for a long time. Intensive research during the last decades has resulted in the identification of a number of effective reagents and catalysts to perform this reaction. Non-stereoselective conjugate alkynylation of unsaturated carbonyl compounds was first achieved by using preformed alkynyl organometallics and later with terminal alkynes under catalytic conditions. These methods paved the way for the development of enantioselective procedures. After initial methods requiring stoichiometric amounts of chiral material, the findings by Corey on Ni-catalyzed addition of alkynylalanes and, particularly, by Carreira on Cu-catalyzed addition of terminal alkynes boosted the research on the development other asymmetric procedures catalyzed by Cu, Zn, Rh, Co, Ru and Pd complexes. The alkynylation of electrophilic alkenes conjugated with groups other than carbonyl and the alkynylation of extended conjugated systems are also discussed in the last part of this review.1 Introduction2 Non-Stereoselective Conjugate Alkynylation of α,β-Unsaturated Carbonyl Compounds3 Enantioselective Conjugate Alkynylation of α,β-Unsaturated Carbonyl Compounds4 Non-Stereoselective and Enantioselective Alkynylation of Other Electrophilic Alkenes5 γ-Alkynylation of α,β-Unsaturated Amides and δ-Alkynylation of Electrophilic Dienes6 Alternative Enantioselective Procedures7 Conclusion and Outlook
Keywords: conjugate addition; alkynes; enones; C–C bond formation; asymmetric catalysis; regioselectivity; electrophilic alkenes